Deep grey matter MRI abnormalities and cognitive function in relapsing-remitting multiple sclerosis. Issue 3 (30th December 2015) - Debernard, Laëtitia; Melzer, Tracy R.; Alla, Sridhar; Eagle, Jane; Van Stockum, Saskia; Graham, Charlotte; Osborne, Jonathan R.; Dalrymple-Alford, John C.; Miller, David H.; Mason, Deborah F.
Abstract: Although deep grey matter (GM) involvement in multiple sclerosis (MS) is well documented, in-vivo multi-parameter magnetic resonance imaging (MRI) studies and association with detailed cognitive measures are limited. We investigated volumetric, diffusion and perfusion metrics in thalamus, hippocampus, putamen, caudate nucleus and globus pallidum, and neuropsychological measures, spanning 4 cognitive domains, in 60 relapsing-remitting MS patients (RRMS) (mean disease duration of 5.1 years, median EDSS of 1.5) and 30 healthy controls. There was significantly reduced volume of thalamus, hippocampus and putamen in the RRMS patients, but no diffusion or perfusion changes in these structures. Decreased volume in these deep GM volumes in RRMS patients was associated with a modest reduction in cognitive performance, particularly information processing speed, consistent with a subtle disruption of distributed networks, that subserve cognition, in these patients. Future longitudinal studies are needed to elucidate the influence of deep GM changes on the evolution of cognitive deficits in MS. Highlights: Grey and white matter parameters were studied in 60 relapsing-remitting multiple sclerosis (MS) patients and 30 healthy controls. There was significantly reduced volume of thalamus, hippocampus and putamen in the MS patients, but no diffusion or perfusion changes. Decreased volume in these deep GM volumes in MS patients was associated with a modest reduction in cognitive performance, particularly information-processing speed. Future longitudinal studies are needed to elucidate the influence of deep GM changes on the evolution of cognitive deficits in MS.